REVISITING CHILD-BASED OBJECTIONS TO COMMERCIAL SURROGACY - Hanna, Jason K. M. (Bioethics, 2010)
Many critics of commercial surrogate motherhood argue that it violates the rights of children. In this paper, I respond to several versions of this objection. The most common version claims that surrogacy involves child-selling. I argue that while proponents of surrogacy have generally failed to provide an adequate response to this objection, it can be overcome. After showing that the two most prominent arguments for the child-selling objection fail, I explain how the commissioning couple can acquire parental rights by paying the surrogate only for her reproductive labor. My explanation appeals to the idea that parental rights are acquired by those who have claims over the reproductive labor that produces the child, not necessarily by those who actually perform the labor. This account clarifies how commercial surrogacy differs from commercial adoption. In the final section of the paper, I consider and reject three further child-based objections to commercial surrogacy: that it establishes a market in children's attributes, that it requires courts to stray from the best interests standard in determining custodial rights, and that it requires the surrogate to neglect her parental responsibilities. Since each of these objections fails, children's rights probably do not pose an obstacle to the acceptability of commercial surrogacy arrangements.